ANALISIS DIVERSIFIKASI INTERNASIONAL : PEMBENTUKAN PORTOFOLIO OPTIMAL INDEKS SAHAM DUNIA (Studi Kasus Pada Indeks Saham Aktif Dunia Versi The Wall Street Journal) - Rony Mahendra; Erwin Dyah Astawinetu (Universitas 17 Agustus 1945 Surabaya, 2019)
The research objective is to establish an optimal portfolio and know the difference between risk and return stock index portfolio candidates and non-candidates. Method used in the preparation of this research portfolio is the single index model, while the samples of this study are active world stock indices version of The Wall Street Journal during the period August 2012 - August 2016 and The Global Dow is used as the benchmark stock index. In establishing the optimal portfolio is used two perspectives: the Rupiah perspective and the U.S. Dollar perspective. The results showed there were three stock indices from the perspective of Rupiah and 8 share index menurutperspektif U.S. Dollar that make up the optimal portfolio, with the cut-of-pointsebesar 0,01393menurut Rupiah perspective and the perspective of 0.0078 US Dollars Based on the perspective of return expectations Rupiah obtained by 0.0258 with a risk of 0.06512. Berdarkan perspective of US Dollars, obtained return expectations at 0.0154 with a risk of 0.0292. From the test results showed that the hypothesis, the return on both perspectives there are significant differences between the index of the candidate, with a non-candidate. Then the risk of stock index, among the candidates, with a non-candidate, the Rupiah perspective there is no difference, but in the perspective of US Dollars, there are significant differences.Keywords: Single Index Model, candidate portfolio, optimal portfolio, expected return, excess return to beta, cut-off-point